Toxicology of aquatic pollution : physiological, molecular and cellular approaches - Taylor, E. W. (Cambridge : Cambridge University Press, 1996)
When this book was first published in 1996, the pollution of the earth's freshwater habitats was, as it is now, a topic of major concern
1. Water chemistry at the gill surfaces of fish and the uptake of xenobiotics -- 2. Bioaccumulation of waterborne, 1,2,4,5-tetrachlorobenzene in tissues of rainbow trout -- 3. Dietary exposure to toxic metals in fish -- 4. The physiology and toxicology of zinc in fish -- 5. Lethal and sub-lethal effects of copper upon fish: a role for ammonia toxicity? -- 6. The physiological status of brown trout exposed to aluminium in acidic soft waters -- 7. Physiological and metabolic costs of acclimation to chronic sub-lethal acid and aluminium exposure in rainbow trout -- 8. Physiological effects of nitrite in teleosts and crustaceans -- 9. Metallothioneins in fish: induction and use in environmental monitoring -- 10. Oestrogenic substances in the aquatic environment and their potential impact on animals, particularly fish -- 11. Effect of genetic toxicants in toxicants in organisms -- 12. In vitro toxicology of aquatic pollutants: use of cultured fish cells -- 13. Principles governing the use of cytochrome P4501A1 measurement as a pollution monitoring tool in the aquatic environment
Includes index
Originally published: 1996
Keywords: Aquatic animals -- Effect of pollution on; Fishes -- Effect of pollution on; Water -- Pollution -- Toxicology